2015
DOI: 10.21273/horttech.25.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alternative Containers for Long- and Short-term Greenhouse Crop Production

Abstract: While research on the use of alternative containers for greenhouse production is growing, most studies have focused on a limited number of types of alternative containers and primarily on short-term greenhouse crops. With the recent release of several new bioplastic alternatives, comparisons to established alternative containers and production of longer rotation ornamental crops should be investigated. Our work, therefore, investigates the performance of ten commercially available alternative container… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…x Means within columns that share lowercase letters or within rows that share uppercase letters are similar by Tukey's honestly significant difference test at P £ 0.05. w Growth index = {plant height + [(diameter 1 + diameter 2)/2]}/2. v growth of plants in bioplastic-based biocontainers was comparable to or greater than plants produced in PP containers (Conneway et al, 2015;Helgeson et al, 2009;Koeser et al, 2013b;Lopez and Camberato, 2011). Although a few inconsistencies in plant growth and quality across a few container types were observed, our results suggest that commercial producers would be able to produce high-quality bedding plants in these bioplasticbased biocontainers, under similar greenhouse conditions or cultural practices.…”
Section: Greenhousesupporting
confidence: 51%
See 1 more Smart Citation
“…x Means within columns that share lowercase letters or within rows that share uppercase letters are similar by Tukey's honestly significant difference test at P £ 0.05. w Growth index = {plant height + [(diameter 1 + diameter 2)/2]}/2. v growth of plants in bioplastic-based biocontainers was comparable to or greater than plants produced in PP containers (Conneway et al, 2015;Helgeson et al, 2009;Koeser et al, 2013b;Lopez and Camberato, 2011). Although a few inconsistencies in plant growth and quality across a few container types were observed, our results suggest that commercial producers would be able to produce high-quality bedding plants in these bioplasticbased biocontainers, under similar greenhouse conditions or cultural practices.…”
Section: Greenhousesupporting
confidence: 51%
“…Through several phases of material development (Liu et al, 2015;Lu et al, 2014;Madbouly et al, 2014;Yang et al, 2015) and greenhouse trials (Currey et al, 2015;Kratsch et al, 2015;McCabe et al, 2014), we identified bioplastics and composites that can be effectively molded into horticultural containers suitable for greenhouse crop production (Grewell et al, 2014). Whereas commercially available bioplastic containers can yield plants of high quality compared with plants grown in PP containers (Conneway et al, 2015;Helgeson et al, 2009;Lopez and Camberato, 2011), our research is the first to report on the effectiveness of novel bioplastic-based biocontainers evaluated by producers.…”
mentioning
confidence: 99%
“…However, certain bioplastic container types, particularly those designed to provide bio-based fertilizer nutrients (Schrader et al, 2013) or to biodegrade after use, exhibited algal growth on the container surface, diminished aesthetic quality, and poorer grower-perceived durability at the end of crop production when compared with petroleum-based plastic containers (Flax et al, 2017). Algal growth on surfaces and variation in container strength of other types of biocontainers (such as peat fiber containers) have been observed by other researchers (Conneway et al, 2015;Evans and Karcher, 2004;Evans et al, 2010). Flax et al (2017) postulated that moisture management during plant production affected the appearance of certain bioplastic containers, and proliferation of algae on the surface of peat-based biocontainers was attributed to irrigation practices and absorption of water by the containers (Evans et al, 2010).…”
mentioning
confidence: 73%
“…Research demonstrates that high-quality potted and annual bedding plants can be produced in biocontainers (Kuehny et al, 2011;Lopez and Camberato, 2011). However, many commercially available biocontainers, particularly those made of bio-based fibers such as peat or coconut coir, are less durable than petroleum-based plastic pots, and their use can result in poor WUE during plant production (Conneway et al, 2015;Evans and Hensley, 2004;Evans et al, 2010;McCabe et al, 2014).…”
mentioning
confidence: 99%
“…Biocontainers, which provide an alternative to petroleum plastic plant containers, can be manufactured from a variety of organic parent materials and vary in both physical and chemical properties (Conneway et al, 2015; Grewell et al, 2014). With new biocontainers entering the commercial market, including some bioplastic containers that release supplemental nutrients as they degrade (Currey et al, 2014(Currey et al, , 2015Schrader et al, 2013) and other biocontainer types whose physical properties influence plant growth by reducing available water to plants (Evans and Hensley, 2004;Evans et al, 2010), we hypothesized that some biocontainer types may influence PGR drench efficacy.…”
mentioning
confidence: 99%